All About Demand-Driven Acquisition - Cramer, Carol Joyner (Taylor & Francis, 2013)
This paper reports on a talk delivered at the Mississippi State University Libraries eResource & Emerging Technologies Summit (LEETS). The author introduces the concept of Demand-Driven Acquisition (DDA) for e-books and explains how it works. The author discusses predicting and controlling costs, as well as other implementation decisions. Finally, the author discusses the possibility of removing books from a DDA program and speculates on some of the effects of DDA on libraries and scholarly publishing.
This is an Author's Accepted Manuscript of an article published in THE SERIALS LIBRARIAN, 2013, available online at: http://www.tandfonline.com/10.1080/0361526X.2013.800631.
Keywords: demand-driven acquisition; academic libraries; e-books